Radar Coincidence Imaging With a Uniform Circular Array - Rui Li; Ying Luo; Qun Zhang; Yi-Jun Chen; Dan Wang (IEEE Access, 2020)
Radar coincidence imaging (RCI), used in conjunction with a uniform circular array (UCA), is presented in this paper. When performing two-dimensional (2-D) imaging for a target, using RCI in conjunction with a uniform linear array (ULA), in three-dimensional (3-D) coordinates, the symmetry phenomenon occurs in certain situation. To overcome this problem, using RCI with a UCA is proposed. First, the symmetry phenomenon of RCI with a ULA and the causes are introduced. Then, the RCI method with a UCA is presented, the signal model is given based on the UCA, and the imaging method is introduced. Finally, the general relationship between the resolution of RCI with a UCA and the independent characteristic of the reference radiation field is analyzed. In view of this, RCI with a UCA has better adaptability to 2-D imaging in 3-D coordinates. Simulation results validate the theoretical analysis and the imaging method.